Outcomes of sexual assault court cases involving people with intellectual disabilities within the Western Cape: the association between conviction of the perpetrator and the complainants level of intellectual functioning - Jantjies, Roslyn Rolien (Department of Psychology, 2023)
People with intellectual disabilities (PWID) are more likely to be survivors of sexual assault than people without intellectual disabilities (ID). Their cognitive, emotional, behavioral, and physical challenges increase their vulnerability and chances of being sexually assaulted. Despite this, individuals that disclose their sexual abuse face multiple barriers while seeking justice. This results in low prosecution and conviction rates of sexual offenders in cases involving complainants with ID. There is limited information available about specific factors that predict a court case outcome of sexual abuse cases involving PWID. This correlational study reviewed archival data of alleged survivors of sexual abuse with ID. The sample of 493 complainants had received assistance from Cape Mental Health (CMH) Sexual and Victim Empowered (SAVE) Program. This study showed that most of the complainants of sexual assault were female (86.8%), and 12.6% were male. Most complainants fell within the Mild ID range (54.6%), followed by Severe (20.3%) and Moderate ID (17%). More than half of the cases were withdrawn (58%), 22% of the perpetrators were found guilty, and 12% were acquitted of the charges. This study found that the ability to understand the consequences of sex and to refuse sexual advances increased the individual's ability to consent to sexual activity, while their ability to answer clarifying questions and take an oath significantly impacted their ability to testify in court. However, neither the ability to provide consent nor the ability to testify was significant in predicting the court case outcomes. This highlights the challenges complainants with ID face when seeking justice for sexual abuse. Sexuality education for PWID may mitigate their risk of sexual abuse and serve as a protective factor. Furthermore, the public's awareness regarding the rights of, and responsibilities towards, PWID may also decrease their vulnerability and protect PWID from injustice.